МОДЕЛЬ ДИНАМІКИ ПІГМЕНТІВ КУЛЬТУРИ МІКРОВОДОРОСТЕЙ У ПЛОТНОСТАТІ - Тренкеншу, Р. П.; Лелеков, О. С. (Marine Ecological Journal, 2023)
A model of the dynamics of the relative content of pigments in cells of microalgae culture is based on the assumption that the observed rate of change of concentration of pigment is the algebraic sum of the rates of synthesis, photodestruction and the rate of recovery of the photo-oxidation pigments. The analysis of obtained equation for given initial and boundary conditions is performed.